Molecular detection and typing of methicillin-resistant Staphylococcus aureus and methicillin-resistant coagulase-negative staphylococci isolated from cattle, animal handlers, and their environment from Karnataka, Southern Province of India - Venugopal, N.; Mitra, S.; Tewari, R.; Ganaie, F.; Shome, R.; Rahman, Habibur; Shome, B.R. (Veterinary World, 2019)
Background and Aim: Methicillin-resistant staphylococci are among the emerging pathogens which have become a threat to both human and animal health. The present investigation intended to examine the occurrence and the molecular characteristics of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant coagulase-negative staphylococci (MRCoNS) recovered from cattle, its handlers, and their environment. Materials and Methods: A total of 666 specimens were subjected to culture method and genus-specific polymerase chain reaction (PCR) for the identification of Staphylococcus. Methicillin resistance was substantiated by PCR identification of mecA and mecC resistance determinants. Species-specific identification of mecA positive isolates was conducted by multiplex PCR. The unidentified species were deciphered by 16S rRNA gene sequencing approach. The mecA positive isolates were further characterized by staphylococcal cassette chromosome mec (SCCmec) typing and multilocus sequence typing (MLST). Results: Duplex PCR identified 728 Staphylococcus isolates, of which 66 (9%) were positive for mecA gene. MRSA constituted 24% of the total mecA positive isolates. Among MRCoNS, Staphylococcus epidermidis (42%), and Staphylococcus haemolyticus (11%) were the most common species identified. Overall, 47% of the mecA positive isolates belonged to SCCmec type V. MLST analysis showed eight different sequence types (STs) among MRSA isolates of which five were novel STs. Among methicillin-resistant S. epidermidis, 19 different STs were found, of which nine novel STs were detected. Conclusion: The increase in the prevalence of mecA positive staphylococci, especially MRCoNS in cattle is a great concern in view of their transmission potential. Hence, continuous monitoring and molecular characterization of methicillin-resistant staphylococci should be elucidated in human and animal sectors so as to prevent the spread of these resistant pathogens.